(untitled) (De Musica, 2021)
Since the late twentieth century, the emergence and development of the Web, digital technologies and streaming media has profoundly influenced the musical world. In this article, I analyse the impact of this transformative process on the presentation, diffusion and reception of opera. Some novelties of contemporary operatic culture include the Met Live in HD and Met Opera on Demand in New York, the Friday Rush at the Royal Opera House in London, the Troisième Scèneof the Opéra de Paris, and the media popularity of the Opening Night (7 December) of the Teatro alla Scala in Milan. From an historical perspective, I also retrace the origins of the long-lasting relationship between opera singers, opera fans, new media and recording technologies. The case of science fiction and literature is particularly thought-provoking. For instance, in his gothic novel Le Château des Carpathes (1892), Jules Verne describes the opera fanaticism of Baron Rodolphe de Gortz: in a gloomy castle in Transylvania, the Baron brings the Italian prima donna La Stilla back to life through projected images and high-quality recordings.